Discovery and optimization of selective RET inhibitors via scaffold hopping. (1st September 2021) - Luo, Zhibo; Wang, Lingli; Fu, Zhifei; Shuai, Bin; Luo, Miaorong; Hu, Guoping; Chen, Jian; Sun, Jikui; Wang, Jiansong; Li, Jian; Chen, Shuhui; Zhang, Yang
Graphical abstract: Abstract: Aberrant alterations of rearranged during transfection (RET) have been identified as actionable drivers of multiple cancers, including thyroid carcinoma and lung cancer. Currently, several approved multikinase inhibitors such as vandetanib and cabozantinib demonstrate clinical activity in patients with RET-rearranged or RET-mutant cancers. However, the observed response rates are only modest and the 'off-target' toxicities resulted from the inhibition of other kinases is also a concern. Herein, we designed and synthesized a series of RET inhibitors based on the structure of selective RET inhibitor BLU-667 and investigated their biological activities. We identified compound 9 as a novel potent and selective RET inhibitor with improved drug-like properties. Compound 9 exhibits a selective inhibitory profile with an inhibitory concentration 50 (IC50 ) of 1.29 nM for RET and 1.97 (RET V804M) or 0.99 (RET M918T) for mutant RETs. The proliferation of Ba/F3 cells transformed with NSCLC related KIF5B-RET fusion was effectively suppressed by compound 9 (IC50 = 19 nM). Additionally, compound 9 displayed less 'off-target' effects than BLU-667. In mouse xenograft models, compound 9 repressed tumor growth driven by KIF5B-RET-Ba/F3 cells in a dose-dependent manner. Based on its exceptional kinase selectivity, good potency and high exposure in tumor tissues, compound 9 represents a promising lead for the discovery of RET directed therapeutic agents and the study of RET-driven tumor biology.